Triazole carboxylic acids as anionic sugar mimics? Inhibition of glycogen phosphorylase by a D-glucotriazole carboxylate - Krulle, T; delaFuente, C; Pickering, L; Aplin, RT; Tsitsanou, K; Zographos, SE; Oikonomakos, N; Nash, R; Griffiths, R; Fleet, G (1997)
Triazole-carboxylic acids related to D-glucose and D-galactose may be prepared by intramolecular [1,3]-dipolar cycloadditions of azides to unsaturated esters, followed by bromine oxidation of the resulting triazoline. Such materials may provide a series of anionic mimics of carbohydrates.